Forensic facial reconstruction: Nasal projection in Brazilian adults. (September 2016) - Tedeschi-Oliveira, Silvia Virginia; Beaini, Thiago Leite; Melani, Rodolfo Francisco Haltenhoff
Highlights: Development of a method for prediction of nose projection. Consistent Literature review. Sample size of 600 lateral cephalographs tested by two observers. Relevant Statistical results. Practical applicability for forensic facial reconstruction. Abstract: The nose has a marked cognitive influence on facial image; however, it loses its shape during cadaveric decomposition. The known methods of estimating nasal projection using Facial Reconstruction are lacking in practicality and reproducibility. We attempted to relate the points Rhinion, Pronasale and Prosthion by studying the angle formed by straight lines that connect them. Two examiners measured this angle with the help of analysis and image-processing software, Image J, directly from cephalometric radiographs. The sample consisted of 300 males, aged between 24 and 77 years, and 300 females, aged 24 to 69 years. The proposed angle ranged from 80° to 100° in both sexes and all ages. It was considered possible to use a 90° angle from projections of the Rhinion and Prosthion points in order to determine the Pronasale position, as well as to estimate the nasal projection of Brazilian adults.